Social and geographical inequalities in the choice of foot therapy as preventive care: A nationwide registry study on Danish people with diabetes - Christine Marie Bækø Halling; Jacob Ladenburg (University of Oslo, 2019)
Diabetic foot ulcers are a serious complication of diabetes with high costs and adverse sequelae, such as lower-extremity amputations. International guidelines recommend that all people with diabetes should have their feet inspected at least once a year. This study is aimed at determining whether socioeconomic factors influence the probability of having the feet inspected by a chiropodist on a nationally representative sample of people with diabetes. We estimate a logit model for the choice determinants of foot inspections among people with diabetes. Of all people with diabetes, 73% have not had their feet inspected by a chiropodist. The results indicate social and geographical inequality with regard to diabetic foot care. Especially for ethnic minorities, people with low income and people living in rural and remote areas. The findings are robust to a series of sensitivity analyses. Published: Online October 2019.